Agriculture Sector approaches to addressing malnutrition. - Webb, Patrick, 1959- (Tufts University. Tisch Library., 2017)
This presentation examines possible solutions for malnutrition sourced from the agriculture sector.; Keywords: USAID, Nutrition Innovation Lab, agriculture, malnutrition Tufts University.; NIL Presentations 2013-2015.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy